2010
DOI: 10.3945/jn.110.123612
|View full text |Cite
|
Sign up to set email alerts
|

Food Groups Associated with a Composite Measure of Probability of Adequate Intake of 11 Micronutrients in the Diets of Women in Urban Mali

Abstract: The prevalence of micronutrient deficiency is high among women of reproductive age living in urban Mali. Despite this, there are little data on the dietary intake of micronutrients among women of reproductive age in Mali. This research tested the relationship between the quantity of intake of 21 possible food groups and estimated usual micronutrient (folate, vitamin B-12, calcium, riboflavin, niacin, vitamin A, iron, thiamin, vitamin B-6, vitamin C, and zinc) intakes and a composite measure of adequacy of 11 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 13 publications
1
50
1
1
Order By: Relevance
“…This measure allows researchers to better capture the whole-diet approach in a quick and low-cost manner. Translating this approach into programs is challenging, however, and researchers are investigating the best assessment tools for evaluating diversity in diets and nutritional outcomes [125,[132][133][134][135].…”
Section: Relying More On Food-based Approachesmentioning
confidence: 99%
“…This measure allows researchers to better capture the whole-diet approach in a quick and low-cost manner. Translating this approach into programs is challenging, however, and researchers are investigating the best assessment tools for evaluating diversity in diets and nutritional outcomes [125,[132][133][134][135].…”
Section: Relying More On Food-based Approachesmentioning
confidence: 99%
“…Hatloy et al, (1998) found no correlation between FVS and DDS with adequacy of micronutrients in children aged 13-58 months. However, other studies did find a positive and significant association between food group diversity and micronutrient adequacy (Rani et al, 2010;Kennedy et al, 2010;Moore et al, 2012).…”
Section: Probability Of Adequacy Of Micronutrientsmentioning
confidence: 88%
“…The main sources of available carbohydrates in our study were starchy staples such as refined white rice, refined wheat flour, bread or millet/sorghum (15) . Variation may occur during the cooking process by modifying the water content and differences in water content will likely account for many of the differences in available carbohydrate content in the food (42) .…”
Section: Discussionmentioning
confidence: 99%
“…The sampling procedure has been described elsewhere (15,16) . Women were selected based on their willingness to participate in the study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation